Diffuse large B-cell lymphoma: an unusual cause of severe otalgia and facial palsy. (15th June 2012) - Reddy, Udaya; Bewick, Jessica; Good, Catriona; Chevassut, Timothy; Das-Purkayastha, Prodip K
Abstract : An elderly woman, two months after chemotherapy for diffuse large B-cell lymphoma, presented with left-sided otalgia, discharge and facial nerve palsy. MRI showed an active left mastoid infection with an ear canal lesion, likely to be a cholesteatoma. However, a biopsy of the mass showed recurrent high-grade lymphoma. Following diagnosis, the patient opted for palliative care within the community and consequently passed away a few weeks later.